Acute Interstitial Nephritis With Karyomegalic Epithelial Cells After Nivolumab Treatment—Two Case Reports. Issue 12 (June 2019) - Ryuzaki, Masaki; Tokuyama, Hirobumi; Uchiyama, Kiyotaka; Nakaya, Hideaki; Hasegawa, Kazuhiro; Miyashita, Kazutoshi; Konishi, Kohnosuke; Hashiguchi, Akinori; Wakino, Shu; Itoh, Hiroshi
Clinical application of immune checkpoint inhibitors (CPIs) including nivolumab is expanding in the field of oncology treatment. Nivolumab is an anti-programmed death 1 protein (PD-1) antibody designed to augment an immunologic reaction against cancer cells. On the contrary, CPIs are known to cause a unique variety of side effects termed as immune-related adverse events, which can affect any organ including kidney. However, the characteristics of renal disorders by nivolumab treatment are poorly described. We describe two cases of acute kidney injury that were treated with nivolumab. Two patients, one with renal-cell carcinoma and the other with lung cancer, exhibited progressive renal dysfunction after the initiation of nivolumab treatment. By kidney biopsy, each case was diagnosed as acute interstitial nephritis (AIN). Of note, tubular epithelial cells enlarged with hyperchromatic nuclei were focally observed, and this finding was consistent with karyomegalic tubular epithelial cells. In immunostaining, most of the enlarged tubular epithelial cells were positive for Ki-67, which suggested regeneration of tubular epithelial cells. Clinically, in one case, renal function was partially recovered with the discontinuation of nivolumab, while in another case renal function was fully recovered with additional corticosteroid treatment. We presented nivolumab-induced AIN with karyomegalic changes of tubular epithelia. We propose that immunosuppressive therapy may be necessary for the full recovery from renal impairment.